In vitro decidualisation of human endometrial stromal cells is enhanced by seminal fluid extracellular vesicles. Issue 1 (1st January 2019) - Rodriguez-Caro, Helena; Dragovic, Rebecca; Shen, Mengni; Dombi, Eszter; Mounce, Ginny; Field, Kate; Meadows, Jamie; Turner, Karen; Lunn, Daniel; Child, Tim; Southcombe, Jennifer Helen; Granne, Ingrid
ABSTRACT: Extracellular vesicles are highly abundant in seminal fluids and have a known role enhancing sperm function. Clinical pregnancy rates after IVF treatment are improved after female exposure to seminal fluid. Seminal fluid extracellular vesicles (SF-EVs) are candidate enhancers, however, whether SF-EVs interact with cells from the endometrium and modulate the implantation processes is unknown. Here, we investigated whether SF-EVs interact with endometrial stromal cells (ESCs) and enhance decidualisation, a requisite for implantation. SF-EVs, isolated from human seminal fluid ( n = 11) by ultracentrifugation, were characterised by nanoparticle tracking analysis and Western blotting, and purified using size exclusion chromatography. Non-decidualised and decidualised primary ESCs ( n = 5) were then treated with SF-EVs. Binding of bio-maleimide-labelled SF-EVs was detected by flow cytometry and fluorescence microscopy. Prolactin and IGFBP-1 protein levels in culture media were also analysed after single and multiple SF-EV exposure. SF-EVs size ranged from 50 to 300 nm, and they expressed exosomal markers (ALIX, SYNTENIN-1, CD9 and CD81). SF-EVs bound to non-decidualised and decidualised ESCs at similar levels. ESCs prolactin secretion was increased after single ( p = 0.0044) and multiple ( p = 0.0021) SF-EV exposure. No differences were found in IGFBP-1 protein levels. In conclusion, SF-EVs enhance in vitro ESC decidualisation and increase secretion of prolactin, an essential hormone in implantation. This elucidates a novel role of SF-EVs on endometrial receptivity.Abbreviations: ECACC: European Collection of Authenticated Cell Cultures; ESCs: endometrial stromal cells; EVs: extracellular vesicles; FCS: foetal calf serum; HRP: horse-radish peroxidase; IFNγ: interferon-gamma; IGF: insulin-like growth factor; IGFBP-1: insulin-like growth factor binding protein 1; IVF: in vitro fertilisation; MVB: multivesicular bodies; NTA: nanoparticle tracking analysis; PRLR −/− : homozygous prolactin receptor knockout; RT: room temperature; SF-EVs: seminal fluid extracellular vesicles; STR: short tandem repeat; TGFβ: transforming growth factor β; uNK: uterine natural killer